Comparison Study on Casein Phosphopeptide-Amorphous Calcium Phosphate Paste and Fluoride Gel on Remineralization of Demineralized Enamel Lesions - Pishehvar, Leila; Mazaheri, Romina; Mirzakhani, Mahboobeh; Nazari, Mohammad Hassan; Ranjbaran, Fatemeh sadat (Journal of Dental School, 2019)
Objective: Tooth surface undergoes continuous remineralization and demineralization. The aim of this study was to compare the effect of Caseinphosphopeptide-amorphous calcium phosphate (CPP- ACP) paste and Fluoride gel on the microhardness of demineralized enamel lesions. Methods: Frothy eight specimens of premolar teeth were chosen and randomly divided to 4 groups of 12. After the initial measurement of micro-hardness the specimens were immersed in demineralizing solution for 4 day and then the measurements were recorded again. Two groups (GL and G3) were treated with CPP-ACP and Fluoride gel respectively according to manufacturer’s instruction. Two other groups (G2 and G4) were treated with CPP-ACP and fluoride gel every week for three months. After the treatments all specimens were taken into PH-cycling and the micro- hardness for each one were measured again. For data analysis, the Repeated Measures ANOVA test and the LSD tests were performed. In each group the percentage of micro-hardness recovery was measured. Results: Repeated Measures ANOVA and LED Test showed that the mean value of hardness was significantly decreased after demineralization in all groups (p=0.01). There was no significant difference in mean hardness value in groups (GL, G3) after treatment (p=0.1, p=0.12) In groups (G2, G4) the mean hardness value were significantly increased (p<0.0001, p=0.1). It is noticeable that the CPP-ACP was significantly more efficient than the fluoride gel. Conclusion: CPP-APC paste and fluoride gel both increase the micro-hardness of enamel when administrated for long time and repeated application.